Teaching game for understanding model: increasing motivation and students’ physical fitness - Syamsuar Syamsuar; Zelhendri Zen (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This study aims to describe the effect of Teaching Game for Understanding (TGfU) in increasing the students’ motivation and physical fitness. TGfU is a training concept of sport based on game. It is not only have meaning as strengthening educational praxis in fields of sport-game separately, but rather to develop an educational approach to the problems solving in tactical strategy in a competition of the sport-game, and also about attitude, motivation, responsibility for the task, collaboration, etc. Method of this study uses a qualitative approach with classroom action research. The results of the study reported that method of TGfU can increase students’ motivation and physical fitness especially in the second cycle of teaching and learning in the field. For sport teacher is advised to use this model in order to improve students’ participation, motivation, tactical cognitive and strategy and sport achievement of their physical fitness, especially for the subject matter of sport required the game approach.